The Canadian party system an analytic history - Johnston, Richard 1948- (UBC Press, 2019)
In this long-awaited book, Richard Johnston combines an arsenal of recently developed analytic tools with a deep understanding of history to makes sense of the Canadian party system
Keywords: Geschichte; Parteiensystem; Kanada; Political parties / Canada; Politics, Practical / Canada; POLITICAL SCIENCE / Political Process / Elections; POLITICAL SCIENCE / Political Process / General; Electronic books